2023
DOI: 10.1097/moo.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral flaps for oral cavity and oropharyngeal reconstruction

Abstract: Purpose of review Oral cavity reconstruction using local flaps is an area of head and neck surgery that has been overshadowed since the introduction of free flaps. Here, we discuss new developments, predominantly modifications to existing techniques for intraoral reconstruction, the utility of different local flaps and a review of functional outcomes. Recent findings The facial artery musculomucosal (FAMM) flap has seen the greatest number of modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, it is imperative to recognize that free flap surgery may be contraindicated in cases where patients are unable to endure prolonged operative times due to underlying comorbidities, such as cardiopulmonary conditions, cardiac issues, or impaired renal function [2,3,10]. In such instances, when feasible, local flap techniques may present a suitable alternative, particularly for small-to moderate-sized intraoral defects [1][2][3][4][5][11][12][13][14][15][16][17]. In a previous study, we reported a successful case involving the use of a single-stage peninsular-shaped lateral tongue flap (pLTF) for reconstructing an intraoral defect following tumor resection in the buccal area, which encompassed the retromolar trigone (RMT) region [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is imperative to recognize that free flap surgery may be contraindicated in cases where patients are unable to endure prolonged operative times due to underlying comorbidities, such as cardiopulmonary conditions, cardiac issues, or impaired renal function [2,3,10]. In such instances, when feasible, local flap techniques may present a suitable alternative, particularly for small-to moderate-sized intraoral defects [1][2][3][4][5][11][12][13][14][15][16][17]. In a previous study, we reported a successful case involving the use of a single-stage peninsular-shaped lateral tongue flap (pLTF) for reconstructing an intraoral defect following tumor resection in the buccal area, which encompassed the retromolar trigone (RMT) region [2].…”
Section: Introductionmentioning
confidence: 99%